Palladium-Catalyzed Ring Opening of Cyclopropane-Appended Spirotricyclic Olefins with Soft Nucleophiles and Organoboronic Acids: Facile Synthesis of Functionalized Spiro[2.4]heptenes - Jijy, Eliyan; Prakash, Praveen; Baiju, Thekke Veettil; Shimi, Manchery; Yamamoto, Yoshinori; Suresh, Eringathodi; Radhakrishnan, Kokkuvayil Vasu (Synthesis, 2014)
The palladium-catalyzed ring opening of cyclopropane- and vinylcyclopropane-appended spirotricyclic olefins by employing active methylene compounds, phenols and organoboronic acids is discussed in detail. The present strategy provides a facile route for the synthesis of biologically significant, functionalized spiro[2.4]heptenes under mild reaction conditions. The synthetic utility of the described compounds is emphasized by the preparation of the corresponding iodolactone derivatives and a highly substituted spiro[2.4]heptane.
Keywords: spirotricyclic olefins; spiro[2.4]heptenes; palladium; phenols; boronic acids